Dignity and respect during pregnancy and childbirth: a survey of the experience of disabled women - Jenny Hall; Vanora Hundley; Bethan Collins; Jillian Ireland (BMC, 2018)
Abstract Background Despite the increasing number of women with disability globally becoming pregnant, there is currently limited research about their experiences. A national survey of women's experience of dignity and respect during pregnancy and childbirth raised concerns about the possibility of women with disability having unequal care with overall less choice and control. To address this further we conducted a study to explore the experiences of dignity and respect in childbirth of women with disability. Methods The study involved a self-selecting, convenience sample of 37 women who had given birth in the United Kingdom and Ireland and had completed an internet-based survey. Women were identified through online networks and groups of and for disabled parents and for people with specific medical conditions. Data were collected using an online survey tool. Survey data were analysed using descriptive statistics. Thematic analysis was used for open questions. Results Despite generally positive responses, just over half of the group of women expressed dissatisfaction with care provision. Only 19% thought that reasonable adjustments or accommodations had been made for them (7/37). When reasonable adjustments were not in place, participants' independence and dignity were undermined. More than a quarter of women felt they were treated less favourably because of their disability (10/37, 27%). At all points in the pregnancy continuum more than a quarter of women felt their rights were either poorly or very poorly respected; however this was greatest in the postnatal period (11/35, 31%). In addition, more than half of the women (20/36, 56%) felt that maternity care providers did not have appropriate awareness of or attitudes to disability. Conclusions Women's experiences of dignity and respect in childbirth revealed that a significant proportion of women felt their rights were poorly respected and that they were treated less favourably because of their disability. This suggests that there is a need to look more closely at individualised care. It was also evident that more consideration is required to improve attitudes of maternity care providers to disability and services need to adapt to provide reasonable adjustments to accommodate disability, including improving continuity of carer.